Comparing genomes: databases and computational tools for comparative analysis of prokaryotic genomes - DOI: 10.3395/reciis.v1i2.Sup.105en - Marcos Catanho; Antonio Basílio de Miranda; Wim Degrave (RECIIS, 2007)
Since the 1990's, the complete genetic code of more than 600 living organisms has been deciphered, such as bacteria, yeasts, protozoan parasites, invertebrates and vertebrates, including Homo sapiens, and plants. More than 2,000 other genome projects representing medical, commercial, environmental and industrial interests, or comprising model organisms, important for the development of the scientific research, are currently in progress. The achievement of complete genome sequences of numerous species combined with the tremendous progress in computation that occurred in the last few decades allowed the use of new holistic approaches in the study of genome structure, organization and evolution, as well as in the field of gene prediction and functional classification. Numerous public or proprietary databases and computational tools have been created attempting to optimize the access to this information through the web. In this review, we present the main resources available through the web for comparative analysis of prokaryotic genomes. We concentrated on the group of mycobacteria that contains important human and animal pathogens. The birth of Bioinformatics and Computational Biology and the contributions of these disciplines to the scientific development of this field are also discussed.